The illusion of permanence : British imperialism in India - Hutchins, Francis G. (Princeton, N.J. : Princeton University Press, 2015)
By combining the techniques of intellectual history and social psychology Professor Hutchins provides a new perspective for an understanding of the intellectual atmosphere of British imperialism in India in the nineteenth century. The author stresses that the illusion of permanence began some years before the Great Mutiny of 1857, although it was the Mutiny that made the subsequent imperialistic attitude rigid. His source materials include the writings of travelers, diarists, civil servants, soldiers, and retired officials; such literature as Jane Eyre, A Passage to India, Oakfield by William Arnold, the Works of Kipling; letters, essays, newspaper articles, and records of the Parliamentary hearings following the Mutiny. Originally published in 1967. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Preface -- Contents -- I. Evangelicism, Utilitarianism, and the Origin of the Idea of a Just Rule -- II. The Right Sort of Conduct: India's Attraction for Victorian Englishmen -- III. Concepts of Indian Character -- IV. The Response to the Mutiny of 1857 and the Abolition of the East India Company -- V. British Indian Society: A Middle Class Aristocracy -- VI. Technology, Force, Democracy -- VII. Nation and Empire -- VIII. The Attempted Orientalization of British Rule -- IX. The Response to the Nationalist Challenge -- X. The Fragility of Imperial Confidence -- Bibliography -- Index
Online resource; title from PDF title page (EBSCO, viewed November 3, 2015)
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Great Britain -- Foreign relations -- India; India -- Foreign relations -- Great Britain; India -- History -- British occupation, 1765-1947.; Grande-Bretagne -- Relations extérieures -- Inde; Inde -- Relations extérieures -- Grande-Bretagne.; Inde -- Histoire -- 1765-1947 (Occupation britannique); POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; HISTORY -- Asia -- India & South Asia; Diplomatic relations; Great Britain; India; 1765-1947; History